Efeitos gastroprotetores do timol em úlceras agudas e crônicas em ratos : evidências do envolvimento das prostaglandinas, canais para potássio sensíveis a ATP e secreção do muco gástrico - Diniz, Polyana Borges França (2016)
Thymol, a monoterpene phenol derivative of cymene, is found in abundance in the essential oils produced by numerous herbs and spices such as thyme (Thymus vulgaris L.), oregano (Origanum vulgaris L.) and Lippia alba (mill.). Several biological effects have been described for thymol such as antioxidant, anti-inflammatory, local anesthetics, antinoceptive, healing and antibacterial properties. It was described the application of thymol in food Science, as herbicidad and inseticides. Moreover, essential oils containing thymol have been used in folk medicine to treat various physiological disorders such as gastrites, indigestion and stomach pains. The present study investigated the gastroprotective actions of thymol (10, 30 and 100 mg/kg, p.o.) in the acute indomethacin and ethanol and chronic acetic acid-induced ulcer models in rats. Some of the mechanisms underlying to the gastroprotective effect of thymol were investigated in the ethanol-induced ulcer model. Gastric secretion parameters (volume, pH, and total acidity) were also evaluted by the pylorus ligature model, and the mucus in the gastric content was determined. The antimicrobial activity against Helicobacter pylori of thymol was performed using the agar-well diffusion method. Thymol produced a dose dependent reduction (p < 0.01) on the total lesion area in the ethanol-induced ulcer model. This gastroprotection was also evaluated microscopically showing that the thymol at all doses decreased the loss of epithelial cells. The gastroprotective response caused by thymol (30 mg/kg) was signigicantly attenuated (P < 0.001) by intraperitoneal treatment of rats with indomethacin (a non-selective inhibitior of cyclo-oxygenase, 10 mg/kg) and glibenclamide (ATP-sensitive K channel blocker), but not by DL-Propargylglycine (PAG, a cystathionine-γ-lyase inhibitor) and Nw-nitro-L-arginine methyl ester hydrochloride (L-NAME, a non-selective inhibitor of nitric oxide synthase). Thymol (30 and 100 mg/kg) also reduced the ulcer index (p < 0.05) and the total lesion area (p < 0.001) in the indomethacin and acetic-induced ulcer models, respectively. In the model of pylorus ligature, the treatment with thymol failed to significantly change the gastric secretion parameters. However, after treatment with thymol (30 and 100 mg/kg) there was a significant increase (p < 0.01) in mucus production. Thymol showed no antimicrobial activity against H. pilory in vitro. Collectively, the present results provide evidence that thymol displays gastroprotective actions on the acute and chronic ulcer models involving mechanisms as increased amount of mucus, prostaglandins, and ATP-sensitive K+ channels.